Influence of Fish Oil-Derived n-3 Fatty Acid Supplementation on Changes in Body Composition and Muscle Strength During Short-Term Weight Loss in Resistance-Trained Men - Philpott, Jordan D.; Bootsma, Niels J.; Rodriguez-Sanchez, Nidia; Hamilton, David Lee; MacKinlay, Elizabeth; Dick, James; Mettler, Samuel; Galloway, Stuart D. R.; Tipton, Kevin D.; Witard, Oliver C. (Frontiers in Nutrition, 2019)
Background: A common detrimental consequence of diet-induced weight loss is muscle loss. Dietary omega-3 polyunsaturated fatty acids (n-3PUFA) exhibit a protective effect on the loss of muscle tissue during catabolic situations such as injury-simulated leg immobilisation. This study aimed to investigate the influence of dietary n-3PUFA supplementation on changes in body composition and muscle strength following short-term diet-induced weight loss in resistance-trained men. Methods: Twenty resistance-trained young (23 ± 1 yrs) men were assigned to a fish oil supplementation group containing 4g n-3PUFA, 18g carbohydrate and 5g protein (FO) or placebo group containing an equivalent carbohydrate and protein content (CON) over a 6 wk period. During wks 1-3, participants continued their habitual diet. During wk 4, participants received all food items to control energy balance and a macronutrient composition of 50% carbohydrate, 35% fat and 15% protein. During wks 5 and 6, participants were fed an energy-restricted diet equivalent to 60% habitual energy intake. Body composition and strength were measured during wks 1, 4 and 6. Results: The decline in total body mass (FO = -3.0 ± 0.3 kg, CON = -2.6 ± 0.3 kg), fat free mass (FO = -1.4 ± 0.3 kg, CON = -1.2 ± 0.3 kg) and fat mass (FO = -1.4 ± 0.2 kg, CON = -1.3 ± 0.3 kg) following energy restriction was similar between groups (all p > 0.05; d: 0.16-0.39). Non-dominant leg extension 1RM increased (6.1 ± 3.4 %) following energy restriction in FO (p < 0.05, d = 0.29), with no changes observed in CON (p > 0.05, d = 0.05). Dominant leg extension 1RM tended to increase following energy restriction in FO (p = 0.09, d = 0.29), with no changes in CON (p > 0.05, d = 0.06). Changes in leg press 1RM, maximum voluntary contraction and muscular endurance following energy restriction were similar between groups (p > 0.05, d = 0.05). Conclusion: Any possible improvements in muscle strength during short-term weight loss with n-3PUFA supplementation are not related to the modulation of FFM in resistance-trained men.